MODEL SCHOOL BRANDING PUSMA GEMILANG MELALUI STRATEGI PEMASARAN DIGITAL DI SD NEGERI PUSMALANG - Azzimatul Hikmah; Mohamad Joko Susilo (Jurnal Manajemen Pendidikan, 2026)
This study aims to examine the PUSMA GEMILANG school branding model through digital marketing strategies at SD Negeri Pusmalang as an effort to strengthen school identity and competitiveness in the digital era. PUSMA GEMILANG represents a value-based branding concept encompassing Achievement, Excellence, Politeness, Independence, Adaptability, and Love of Learning as reflections of the school’s character and strengths. This research employed a qualitative approach using a library research method by analyzing relevant academic literature, journal articles, books, and online documents related to digital marketing, educational branding, and school promotion practices, including the social media activities of SD Negeri Pusmalang. Data were analyzed using content analysis through the stages of data reduction, data display, and conclusion drawing. The findings indicate that digital marketing strategies integrated with the values of PUSMA GEMILANG effectively build a strong, authentic, and consistent school image in the public sphere. The utilization of social media platforms, visual and multimedia content, personal branding of teachers and the principal, and digital interaction with parents has contributed to increased visibility, public trust, and community interest in the school. Therefore, the PUSMA GEMILANG branding model implemented through digital marketing serves not only as a promotional tool but also as a strategic approach to strengthening educational quality, school identity, and sustainable reputation at SD Negeri Pusmalang.